Finite Element Analysis for Upper Molar Distalization - Liliana Ioana Vata; Cristel Stirbu; Irina Zetu; Mariana Pacurar (Romanian Society of Oral Rehabilitation, 2012)
Orthodontic literature indicates that upper molar distalisation is a tipping and extrusion movement, combined with mesio-buccal rotation and buccaly-crown torque, depending on the distalisers used. FEM (finite element method) allow a simulation of force systems which can determine bodily distal molar movement. Using FEM we can also determine the role of second and third molar during upper first molar distalisation movement. This study presents a model of upper first molar, periodontal ligment and alveolar bone using the analysis and design programmes Solidworks2007 and CATIA P3V5R16. Our results using FEM shows that the rotational axis of first molar is displaced when applying a palatal force for distalisation from buccaly - apex to palatal - crown and compressive stress is located on cervical region of distobuccal root. For bodily movement, the moment/force ratio at the molar centre of resistance must be zero, so it is necessary to reduce the moment on the molar band using a counterbalancing couple (CBC) with effects in vertical plane. The displacement of upper molar rotational axis during distalisation is proved by molar rotation and explains the second molar role as a fulcrum, when is not erupted. In conclusion, bodily distal upper molar movement could be obtained only when rotational axis is at infinite and the compressive stress is homogeneously distributed in the periodontal ligament.